Cohesion in Descriptive Discourse Written by The Sixth Semester Students of The English Department of FPBS IKIP Ujung Pandang - Haryanto Atmowardoyo; Geminastiti Sakkir (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2023)
This study of cohesion in descriptive discourse was written by students of the English Department of FPBS IKIP Ujung Pandang. This study describes the types of cohesion used in the students’ discourse and the degree of cohesive harmony of the discourse. It is drawn from the facts that this type of cohesion occurs very frequently in every student’s discourse. Cohesion in the students’ discourse does not function well as the foundation of coherence, drawn from the degree of cohesive harmony of the students’ discourse. As mentioned, the degree of cohesive harmony of the students’ discourse is low. The low degree of cohesive harmony expresses that the cohesion of the discourse does not function well as the foundation of coherence. It reflects that, in general, the students do not stay long enough on the similar things they are on about.